Respon Terhadap Pujian Menggunakan Continuum Hypothesis (Studi Kasus: Mahasiswa Linguistik Program Pascasarjana Universitas Diponegoro) - Herri Susanto (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2012)
Compliment respond is an interesting topic to discuss for researchers in many parts of the world. This happened because different areas have different ways of responding. This article will discuss compliment responds using Continuum Hypothesis which was identified from 13 compliment responds of Diponegoro University postgraduate students. Questionaires were distributed to 13 students and then the researcher identified the data quantitatively and qualitatively. The results found not only 13 responds using Continuum Hypothesis strategies for replying compliments furthermore 10 responds of situation also formed new compliment strategies such as Joke, Suspicious, and Explanation followed by question strategies.